Peningkatan Eksistensi Produk dan Digital Marketing pada Koperasi Tenun Pandai Sikek Kec. X Koto Kab. Tanah Datar - Rizka Hadya; Irdha Yusra; Yulistia Yulistia; Novi Yanti; Dina Adawiyah; Delori Nancy Meyla (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
The contribution of the Pandai Sikek Weaving Cooperative to the development of the community's economy is very large considering that most of the people whose business scale belongs to this home business group are widely found in the environment, especially in Pandai Sikek Sepuluh Koto (X Koto) District, Tanah Datar Regency, West Sumatra. The purpose of this activity is to make the product packaging more attractive and durable and can avoid product damage, but it also aims to market products using digital marketing. The implementation of this service begins with a pre-survey of the location. Furthermore, entrepreneurship training and cooperative marketing and financial management programs were carried out. The method of implementing the activities to be carried out in the community services program is in accordance with the field of problems handled in the cooperative. The community services activities carried out produced several outputs, namely the availability of unique product packaging to be the hallmark of products produced by Pandai Sikek Weaving Cooperatives, as well as the existence of marketing and promotional media based on digital marketing so that the market share of weaving craftsmen's products becomes wider. The other hand, activities can also improve the expertise of the Pandai Sikek Weaving Cooperative in skills and marketing products.